2020
DOI: 10.3390/jcm9051431
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Patients with Elizabethkingia Infection and the Clinical Impact of the Antimicrobial Susceptibility Patterns of Elizabethkingia Species

Abstract: Elizabethkingia species (spp.), which can colonize hospital environments, are emerging nosocomial pathogens presenting high mortality. Due to their intrinsic resistance to a broad range of antibiotics, optimal antibiotic dosage has yet to be determined against infections caused by Elizabethkingia spp. This study aimed to investigate the risk factors for the mortality of infections caused by Elizabethkingia spp. and assess the clinical implications of their antimicrobial susceptibility patterns. Data from 210 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 51 publications
0
14
0
1
Order By: Relevance
“…The Gram-negative bacteria of the genus Elizabethkingia have recently emerged as an important pathogen in hospital-acquired infections and are generally associated with high mortality [ 1 ]. Recent literature has reported several cases of severe infection in humans owing to this organism, with neonatal meningitis most commonly presented in children [ 2 ], accompanied by a range of other clinical manifestations such as septicemia and bacteremia [ 3 , 4 ], osteomyelitis [ 5 ], urinary tract infections [ 6 , 7 ], endogenous endophthalmitis [ 8 ], endocarditis [ 9 ], epididymo-orchitis [ 10 ], pulmonary abscess [ 11 ], necrotizing fasciitis [ 12 , 13 ], cystic fibrosis [ 14 ], hydrocephalus [ 15 ], and secondary infections with a high mortality rate, particularly in immunocompromised patients [ 16 ]. Elizabethkingia meningoseptica infections have also been associated with COVID-19 patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Gram-negative bacteria of the genus Elizabethkingia have recently emerged as an important pathogen in hospital-acquired infections and are generally associated with high mortality [ 1 ]. Recent literature has reported several cases of severe infection in humans owing to this organism, with neonatal meningitis most commonly presented in children [ 2 ], accompanied by a range of other clinical manifestations such as septicemia and bacteremia [ 3 , 4 ], osteomyelitis [ 5 ], urinary tract infections [ 6 , 7 ], endogenous endophthalmitis [ 8 ], endocarditis [ 9 ], epididymo-orchitis [ 10 ], pulmonary abscess [ 11 ], necrotizing fasciitis [ 12 , 13 ], cystic fibrosis [ 14 ], hydrocephalus [ 15 ], and secondary infections with a high mortality rate, particularly in immunocompromised patients [ 16 ]. Elizabethkingia meningoseptica infections have also been associated with COVID-19 patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a higher CRP to albumin ratio at admission has been determined as a risk factor for in-hospital mortality in elderly patients with acute kidney injury requiring dialysis (21). Similarly, an initial elevated CRP to albumin ratio was significantly related to 28-day mortality associated with infections caused by Elizabethkingia spp., a dangerous opportunistic bacterial pathogen causing different illnesses including pneumonia (22). The authors concluded that the prediction of clinical courses using an initial CRP to albumin ratio is a priority to reduce the mortality in these patients.…”
mentioning
confidence: 99%
“…found that rifampin is unproductive to against E. anophelis , and the susceptibility rate was only 20.5% ( Chang et al., 2021 ). Nevertheless, in most other studies, it was reported that rifampin is potent in fighting E. anophelis bacteria; even more than 95% of strains remained sensitive ( Han et al., 2017 ; Seong et al., 2020 ; Wang et al., 2020 ; Chiu et al., 2021 ). Corresponding to these reports, rifampin also showed high in vitro activity inhibiting E. anophelis in our study.…”
Section: Discussionmentioning
confidence: 91%